O patchwork literário de Paulina Chiziane e Toni Morrison : um estudo comparativo entre Niketche : uma história de poligamia e Beloved - Albuquerque, Soraya do Lago (2014)
Postcolonial literatures are characterized by granting voice to the marginalized , who are considered subaltern and the minorities for those, through the multiple voices which are expressed by literary writing can be heard and so it can be able to find so awaited autonomy and significance as a historical human being . It is in this context that the two writers are inserted in which they are the focus of this study which intend to do a comparative study between the works of the two writers of African countries : Paulina Chiziane , moçambiquean and Toni Morrison , American and African descent . Both express through the literature the customs of their people , triggering memories through a narrative flow through the traces left by the orature . The women1s inclusion in the literary world was one of the innovations of postcolonial literatures of African countries and African descent ones because until there the woman neither express their needs nor their outrage , especially by the social building , political and historical of the patriarchal and sexist society. With the colonial subjugation it couldn’t be be heard at all. Instead of this, the emotions were muted in their secluded , waiting for the moment to change it into empowerment the voice in literature and, in action, the feminist political activities . Trusting in that empowerment which was given to the literature we intend to show how the two writers appropriated their characters with it and we also goal to get the dialogue with the changing proposals and the subversion of the setting in which they find themselves.